Alcide De Gasperi e la costruzione della «nostra patria Europa» - Leonardo Brancaccio (Democrazia e Diritti Sociali)
May 9, 2025, marked the 75th anniversary of Europe Day. The article describes the valuable contribution made by Italian statesman Alcide De Gasperi to the construction of what he called «our homeland Europe»: a path that starts from the programmatic document Reconstructive Ideas of Christian Democracy, drafted by the Trentino politician and printed in July 1943. A paragraph in the document is dedicated to Italy’s position in the «International Community» and the «European Community» and continues up to the last months of De Gasperi’s life, when, on the occasion of the Fifth National Congress of the Christian Democracy (Naples, June 26-29, 1954), he affirms that the European community means «peace» De Gasperi, co-founding father of the Italian Republic and the European Union, outlines what Europe’s vocation is: to be a builder of peace and unity.